PRAKTIK KERJA SAMA BISNIS AYAM POTONG PERSPEKTIF EKONOMI SYARIAH DI KECAMATAN JEKAN RAYA - Sukmana, Enriko Tedja; Mandalika, Sri (Fakultas Ekonomi dan Bisnis Islam IAIN Palangka Raya, 2017)
The purpose of this research was to answer these problems. Based on the above issues, this type of research in this thesis was using qualitative research with descriptive approach. Data collection techniques in this research were interview, observation and documentation. The result of this research, namely: (1) cooperation practice of meat-producing chicken was done by the supplier (capital contribution) and managers (capital contributions and skill) with the provisions of the results namely: IDR 1,200 per kilograms (stuck). (2) the cooperation practice of meat-producing chicken business in Jekan Raya District was incompatible with Musharaka contract because the the result obtained before acquiring the real advantage and the disadvantages were not divided according to the capital portions of both parties.